Infection and morphology of parasitic protozoan Nematopsis sp. in banana prawn (Penaeus merguiensis) from Wonnapa Beach Pier, Bangsaen, Chonburi Province, Thailand - เสริมทรัพย์ วริศรา (Journal of Science and Technology Songkhla Rajabhat University, 2022)
Infection and morphology of parasitic protozoan Nematopsis sp. in banana prawn from Wonnapa Beach Pier, Bangsaen, Chonburi Province has been conducted during May 2012 and January 2013. Out of the 240 samples examind, 63.33% were infected by Nematopsis. In details, the prevalence of Nematopsis infection found in male and female samples of P. merguiensis was 62.5 and 64.61, respectively. From this study, a few different stages of Nematopsis infection in Penaeus merguiensis could be divided into three stages: Gamont, Syzygy and Gametocyst. syzygy of Nematopsis was very common with the highest prevalence (63.33%), followed by Gamont (10%) and Gametocyst (4.17%)